Development of the calf grimace scale for pain and stress assessment in castrated Angus beef calves - Farghal, Mostafa; Pajor, Ed; Luna, Stelio P. L. [UNESP]; Pang, Daniel; Windeyer, M. Claire; Ceballos, Maria Camila (Springer Nature, 2024)
Grimace scales have been used to assess pain in various animal species. This study aimed to develop the calf grimace scale (CGS), evaluate its responsiveness and the effect of external factors (change of environment and dam separation, and restraint) on CGS. Sixty-nine Angus calves, 6–8 weeks old, were randomly allocated into castrated (n = 34) and sham castrated (n = 35) groups. Images were extracted from videos pre- (M1-M4), during- (M5), and post-castration/sham castration (M6, M7). Six facial action units (FAUs) were identified: ear position, orbital tightening, tension above the eye, nostril dilation, straining of chewing muscle, and mouth opening. Final CGS median scores increased after castration (P < 0.001) for both non-restrained (M7 versus M2) and restrained (M6 versus M3) calves, indicating scale responsiveness. Final CGS median scores increased (P < 0.001) when calves were subjected to external factors before castration (M1 [baseline] versus M2 and M3). However, there was no difference (P > 0.05) in CGS median scores before and after sham castration, regardless of restraint (M3 versus M6, and M2 versus M7), indicating that the external factors may have reached a maximum effect. The CGS is composed of six FAUs, responsive to acute pain and can identify stress unrelated to pain.
Keywords: Animal welfare; Dam separation; Facial action units; Restraint